The Analysis of Chitosan Granules of Polymesoda Erosa on Catfish - Ariyanti Ariyanti; Eni Masruriati; Lina Lisiana Pasha; Dina Arlidina (Indonesian Journal of Global Health Research, 2021)
These abundant polymesoda erosa are only a waste for the community and have not been widely used by the community. Polymesoda erosa waste can be used because it includes local raw materials that are easily available and often found as waste for the community. The compounds contained in the shells of polymesoda erosa are chitin, calcium carbonate, calcium hydroxyapatite and calcium phosphate. This research was conducted to utilize the waste of polymesoda erosa as a granule supplement for catfish feed. The purpose of this study was to determine the most optimal concentration of chitosan waste granules from polymesoda erosa shells as catfish feed. This research is a laboratory experimental study using a completely randomized design with 5 treatments. The treatment applied was the difference in the concentration of chitosan shells from polymesoda erosa shells by 15%, 25%, and 35%, with negative control and positive control. The parameter in this study was the increase in weight of catfish. Observations were made for 1 month by feeding 3 times. To determine the existence of a comparison, a statistical test was carried out using One Way Anova test. The results showed that the optimal concentration of chitosan granules from polymesoda erosa waste was at the concentration of 35% by observing the development of fish weight.